Pandemic, prisons and Criminal Law: When the Courts are not up to par. Comments to Order AP1073-2020 of June 3, 2020 (51983) of the Supreme Court of Justice (2020)
This work reflects on the Auto AP10732020 of June 3, 2020 (rad. 51983) of the Criminal Cassation Chamber of the Supreme Court of Justice, an order in which one of the requests submitted regarding the application of the exception of unconstitutionality against article 6 of Legislative Decree 546 of 2020, issued by the National Government in the framework of the pandemic caused by Covid19. Afterwords, a review about the principles of necessity and proportionality in relation to the case is given.